Analisis Komparasi Manajemen Risiko Pada Koperasi Syariah dI Kabupaten Boyolali - Abdul Haris Romdhoni (ITB AAS INDONESIA Surakarta, 2016)
This study aims to determine the risk of what is on of financing in Islamic financial institutions in Boyolali especially sharia cooperatives and how to handle them. This research is a descriptive study using primary data obtained from interviews, excavation documentation and supporting information as well as a qualitative research.Mudaraba is a contract and products of Islamic institution. Mudaraba of financing is one of a number of financing in Islamic financial institutions that have a high risk. With such high risk need careful risk management so that losses can be minimized. Obviously the first step is what and how these risks are addressed. Based on the findings in the field of risk control is done in the first three stages, before financing, both when financing and the third is after financing.Keyword : financing, mudaraba,risk and return